2014
DOI: 10.1038/srep07487
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pathogenic non-enveloped viruses by 25-hydroxycholesterol and 27-hydroxycholesterol

Abstract: Recent studies reported a broad but selective antiviral activity of 25-hydroxycholesterol (25HC) against enveloped viruses, being apparently inactive against non-enveloped viruses. Here we show that 25HC is endowed with a marked antiviral activity against three pathogenic non-enveloped viruses, i.e. human papillomavirus-16 (HPV-16), human rotavirus (HRoV), and human rhinovirus (HRhV), thus significantly expanding its broad antiviral spectrum, so far recognized to be limited to viruses with envelope. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 21 publications
3
96
0
1
Order By: Relevance
“…25HC has been reported as a potent antiviral mediator against a panel of enveloped and nonenveloped virus (20,21,31,47). However, these studies differ in their conclusions about the exact antiviral mechanism.…”
Section: Discussionmentioning
confidence: 70%
“…25HC has been reported as a potent antiviral mediator against a panel of enveloped and nonenveloped virus (20,21,31,47). However, these studies differ in their conclusions about the exact antiviral mechanism.…”
Section: Discussionmentioning
confidence: 70%
“…The oxysterol 25HC is a metabolite of cholesterol produced and secreted by macrophages and has multiple effects on lipid metabolism. Recently, 25HC was reported to be a potent antiviral mediator against various kinds of viruses (25,26). In this study, the addition of 25HC drastically inhibited SFTSV growth, particularly the inhibition of virus entry ( Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Both studies confirmed broad antiviral activity of 25HC in vitro against different classes of lipid-enveloped RNA and DNA viruses. This was subsequently reaffirmed by several independent studies (Arita et al 2013;Chen et al 2014;Mboko et al 2014), and the antiviral activity was additionally extended to nonenveloped viruses (Civra et al 2014). Table 1 summarizes the viruses whose susceptibility to 25HC's antiviral effects has been validated.…”
Section: Hc: Broad Antiviral Lipid Effectormentioning
confidence: 57%